Physiological feedback technology for real-time emotion regulation: a systematic review - Sun, Yifan; Lu, Tian; Wang, Xuanyi; Chen, Wanlin; Chen, Shulin; Chen, Hang; Zheng, Jing (Frontiers in Psychology, 2023)
Background: Previous studies suggest that physiological feedback can be an effective method for emotion regulation (ER). However, studies on the specific effects of physiological feedback have shown conflicting results due to inconsistencies in study designs. Therefore, we present this systematic review to further validate the effectiveness of physiological feedback for ER, clarify its specific effects, as well as summarize the factors that influence its effectiveness. Method: This systematic review following PRISMA guidelines covers all studies using physiological feedback in emotions. A literature search was conducted in Web of Science, PubMed, PsychINFO, China National Knowledge Infrastructure, and WANFANG DATA. And a standardized quality assessment was performed. Results: We identified 25 relevant studies, and the majority of these studies showed a significant regulatory effect of physiological feedback on different emotions. The feedback’s content, explanation, authenticity, real-time capability, and modality were the key factors that influenced its effects, and this technology will achieve its optimal ER effect when these factors are considered comprehensively. Conclusions: These findings further confirmed the effectiveness of physiological feedback as an ER method, as well as providing key factors that should be addressed in its application. Meanwhile, due to the limitations of these studies, more well-designed studies are still needed.